Relationship Between Research Training, the Strengthening of Autonomous Learning and Time Management in Undergraduate Medical Education - Martínez-Sánchez, Lina Maria; Molina-Valencia, Juliana Lucía; Rodríguez-Padilla, Libia María; Ruiz-Rodríguez, Juan Pablo; Jaramillo-Jaramillo, Laura Isabel (Revista Electrónica Educare, 2022)
Introduction. In medical education, it is important to develop competencies that encourage learning to learn through flexible strategies such as research training. Objective. To determine the relationship between research training, autonomous learning strengthening, and medical students’ time management. Methodology. A mixed-design study with quantitative (transversal analytical) and qualitative (focus groups and interview) components. In the study participated 110 last semesters students who signed an informed consent document. A sociodemographic-academic instrument, a scale of preparation for independent learning, and time management instrument were applied. A descriptive analysis of the variables was conducted, and the scores obtained were compared among students linked or not to research processes through the student’s t-test. Results. Of the participants, 60.6% were women, 94.5% did not work, and 85.5% came from private schools. Most students have access to computers and internet services, 96.4% and 98.2%, respectively. Students linked to research processes obtained higher scores on the scale of independent learning than those who were not linked (Difference in means: 7, IC95%: 1-13, p = 0.02) in aspects related to the desire to learn (p = 0.004). In the same way, there were marginal differences in time management (Difference in means: 4.3, 95% CI: 0.2-8.5, p = 0.04), related to short-term planning (p = 0.03). In the interviews and focus groups, the students highlighted the competencies in the critical analysis developed in research courses. Conclusions. Students linked to research processes have higher scores on the EPAI and TQM scales, showing that research enhances skills related to self-directed learning and time management.